An Empirical Evaluation of a Composite Heterogeneous Model of Brand Choice and Purchase Timing Behavior - Zufryden, Fred S. (Management Science, 1978)
In a previous article, a new model of brand choice and purchase timing behavior has been discussed with respect to its theoretical foundations and mathematical development (Zufryden, F. S. 1977. A composite heterogeneous model of brand choice and purchase timing behavior, theoretical development. Management Sci. 24 (2, October).). This article first develops a new statistical methodology to estimate the model's parameters. Then, the model is empirically evaluated and compared to several previous stochastic models in an actual market situation. The empirical evidence provides strong support of the viability of the proposed model given its ability to describe and predict measures of market behavior and product performance that are of importance to marketing managers. Such measures of market behavior as the cumulative penetration, trial and repeat purchase patterns of a chosen brand all appear to coincide closely with actual data.